ChemInform Abstract: Facile Route to 2‐Fluoropyridines via 2‐Pyridyltrialkylammonium Salts Prepared from Pyridine N‐Oxides and Application to 18F‐Labeling. Issue 49 (December 2015) - Xiong, Hui; Hoye, Adam T.; Fan, Kuo‐Hsien; Li, Ximin; Clemens, Jennifer; Horchler, Carey L.; Lim, Nathaniel C.; Attardo, Giorgio
Abstract: Starting from pyridine N‐oxides the formation of various 2‐trialkylammonium salts is examined.